Figurative language in songs for English Learning - Elvara Artamevya Raharjo Putri; Taufiq Effendi; Syarifah Azharina Syafrudin (Mitra Palupi, 2022)
Background: Songs have long been popular literary works for learning English. One way is by paying attention to figurative language used in songs popular among EFL learners. Purpose: This study was aimed at identifying the types of figurative language used in songs recently popular among Indonesian youth. Design and methods: The data were purposively collected from a sample of three songs of a famous album. The data were qualitatively analysed by using Gorys Keraf’s theory. Results: Finally, it is recommended that types of figurative language need to be taught to and learned by EFL learners to help enhance their comprehension when dealing with popular literary works like songs.